pH-Dependent Behavior of Novel 5-FU Delivery System in Environmental Conditions Comparable to the Gastro-Intestinal Tract - Geza Lazar; Fran Nekvapil; Branko Glamuzina; Tudor Tamaș; Lucian Barbu-Tudoran; Maria Suciu; Simona Cinta Pinzaru (MDPI AG, 2023)
A biogenic carrier for 5-fluorouracil (5-FU) loading and subsequent tableting as a new drug formulation for slow release has been proposed using the biomineral from blue crab carapace. Due to its highly ordered 3D porous nanoarchitecture, the biogenic carbonate carrier could achieve increased effectiveness in colorectal cancer cure provided that the formulation would successfully pass through the gastric acid conditions. Following the recently proven viability of the concept by demonstrating the slow release of the drug from the carrier using the highly sensitive SERS technique, here we investigated the 5-FU release from the composite tablet drug in pH conditions replicating the gastric environment. The released drug from the tablet was studied in solutions with three relevant pH values, pH 2, pH 3, and pH 4. The 5-FU SERS spectral signature for each pH value was used to build calibration curves for quantitative SERS analysis. The results suggested a similarly slow-releasing pattern in acid pH environments to that in neutral conditions. Although biogenic calcite dissolution was expected in acid conditions, the X-ray diffraction and Raman spectroscopy showed preservation of calcite mineral along with the monohydrocalcite during acid solution exposure for two hours. The total released amount in a time course of seven hours, however, was lower in acidic pH solutions, with a maximum fraction of ~40% of the total amount of loaded drug, for pH 2, as opposed to ~80% for neutral values. Nonetheless, these results clearly prove that the novel composite drug retains its slow-releasing character in environmental conditions compatible with the gastrointestinal pH and that it is a viable and biocompatible alternative for oral delivery of anticancer drug to reach the lower gastro-intestinal tract.